Impact of high body mass index on hepatocellular carcinoma risk in chronic liver disease: A population-based prospective cohort study. - Moonho Kim; Baek Gyu Jun; Hwang Sik Shin; Jee-Jeon Yi; Sang Gyune Kim; Sang-Wook Yi (PLoS ONE)
Background and aims We investigated associations between body mass index (BMI) and hepatocellular carcinoma (HCC) in patients with hepatitis B (HBV) C (HCV) virus infection, alcoholic liver disease (ALD), non-alcoholic fatty liver disease (NAFLD), and liver cirrhosis (LC). Methods We followed 350,608 Korean patients with liver disease who underwent routine health examinations from 2003-2006 until December 2018 via national hospital discharge records. Multivariable adjusted hazard ratios (HRs) per 5-kg/m2 BMI increase (BMI ≥25 kg/m2) for HCC risk were calculated using Cox models. HCC developed in 17,752 patients. Results The HRs (95% CI) were 1.17 (1.06-1.28), 1.08 (0.87-1.34), 1.34 (1.14-1.58), 1.51 (1.17-1.94), and 1.11 (1.00-1.23) for HBV, HCV, ALD, NAFLD, and LC, respectively. The HRs for HBV were 1.45 (1.23-1.70) and 1.06 (0.95-1.19) in women and men, respectively; the corresponding HRs for LC were 1.27 (1.07-1.50) and 1.02 (0.90-1.16), respectively. In patients <65 years old with HBV, HCV, and NAFLD, the HRs were 1.17 (1.07-1.29), 1.33 (1.03-1.73), and 1.20 (0.87-1.64), respectively; the corresponding HRs were 1.05 (0.70-1.59), 0.74 (0.50-1.10), and 2.40 (1.62-3.54), respectively, in patients ≥65 years old. A BMI of 27.5-29.9 kg/m2 showed significantly higher HCC risks in patients with HBV, ALD, NAFLD, and LC. Conclusions Higher BMIs were associated with increased HCC risks in patients with HBV, ALD, NAFLD, and LC. Overweight status increased HCC risk. Women with HBV and LC had stronger BMI-HCC associations than men. The effect of high BMI was stronger in older patients with NAFLD and younger patients with viral hepatitis.